Energy, exergy, economic and exergoenvironmental analyses of polygeneration system integrated gas cycle, absorption chiller, and Copper-Chlorine thermochemical cycle to produce power, cooling, and hydrogen. (1st May 2021) - Fan, Guangli; Ahmadi, A.; Ehyaei, M.A.; Das, Biplab
Abstract: The proposed cogeneration system consists of a gas cycle, an absorption chiller, a heat recovery steam generator (HRSG), and Copper-Chlorine ( Cu-Cl ) thermochemical cycle that is applied for power, cooling, and hydrogen production. The configuration of these cycles is somehow that the exhaust hot gas from the gas cycle operates a heat recovery steam generator (HRSG), which is considered to produce steam for the Cu-Cl cycle. Then, the rest of the heat of hot gas energy is recovered by an absorption chiller for producing a cooling capacity. In this cycle, minimum exhaust heat from the gas turbine delivers to the atmosphere and causes less thermal population and clean power generation. Moreover, providing cooling capacity and hydrogen production associated with this cogeneration is applicable to store hydrogen as a clean fuel. A comprehensive performance assessment of this cogeneration system has been carried out based on energy, exergy, economic, and exergoenvironmental analyses. The results revealed while energy and exergy efficiencies for the gas cycle alone are 19% and 15%, respectively, and with using this proposed plant, these values can be improved up to about 43% and 44%, respectively. Economic analysis of this system shows the simple payback period (SPP) value for the stand-alone gas cycle is about 7.2 years, whereas this index for the combined gas and Cu-Cl cycles is about 3.1 years and for the whole system is 2.4 years. The results of exergoenvironment analysis reveal that the highest exergy stability factor (exergy destruction) of 0.8 belongs to the Cu-Cl cycle and the lowest exergy stability value of about 0.03 belongs to the absorption chiller cycle. Highlights: Introducing the new configuration cycle to produce electricity, cooling, and hydrogen. Energy, exergy, economic, and exergoenvironmental (4E) analyses of cycle. The proposed system energy efficiency is 43%. The proposed system exergy efficiency is 44%. The proposed system payback period is 2.5 years.